Lazismu and Remaking the Muhammadiyah’s New Way of Philanthropy - Zakiyuddin Baidhawy (Al-Jami'ah Research Centre, 2015)
This study is aimed to analyze the new way of philanthropy by special reference to Lembaga Amil Zakat Infak dan Sadaqah Muhammadiyah (Muhammadiyah Philanthropic Board: hereafter Lazismu); explore the measures taken by Lazismu to promote empowerment and social justice movements by combining charity and entrepreneurship; and understand the motive of the new philanthropy movement initiated by Lazismu. Through the ‘third way’ approach and analysis, this study found that: first, Muhammadiyah, as a non-profit social-religious organization, admits its role as an agent of transformation vis-à-vis the State. Lazismu is able to show its flexibility to adapt to new trends in philanthropy. Lazismu is also able to initiate breakthrough in management of Zakat, Infaq, and Sadaqah and move them beyond charity activities to productive and redistributive activities to promote social justice and equity. Second, Lazismu shows creativity and sophisticated programs exceeding the expectations of muzakki (alms payer), benefactor, and donors. Realization of philanthropy programs developed by Lazismu extends from education development, agriculture development, youth entrepreneurship, and women empowerment, to Masjid based community empowerment. Third, Lazismu combines theology of love, generosity, and voluntarism to produce transformative philanthropy that is successful to alter charity oriented generosity to creative and innovative good deeds.[Kajian ini dimaksudkan untuk melihat model filantropi baru pada Lazismu (Lembaga Amil Zakat Infak dan Sadaqah Muhammadiyah); mengungkapkan langkah-langkah yang diambil oleh Lazismu untuk melakukan pemberdayaan dan keadilan sosial; dan untuk memahami tujuan filantropi baru yang digagas oleh Lazismu. Menggunakan pendekatan dan analisis “Jalan Ketiga”, makalah ini menemukan bahwa Muhammadiyah, sebagai organisasi non-profit, mengakui perannya sebagai agen perubahan vis-a-vis Negara. Lazismu mampu menujukkan fleksibilitas untuk beradaptasi dengan mode-mode filantropi baru. Lazismu juga mampu menemukan terobosan-terobosan dalam manajemen zakat, infak, dan sedekah. Lazismu mengelolanya dari sekedar kegiatan kedermawanan menjadi kegiatan-kegiatan produktif dan redistributif untuk mewujdukan kesetaraan dan keadilan sosial. Kedua, Lazismu menunjukkan kreatifitas dan program-program canggih melampaui harapan muzakki, donor, dan penerima. Wujud program filantropi yang dikembangkan oleh Lazismu meliputi pengembangan pendidikan, pembangunan pertanian, kewirausahaan pemuda, dan pemberdayaan perempuan, sampai dengan pemberdayaan masyarakat berbasis masjid. Ketiga, Lazismu mengkombinasikan teologi kasih, kebajikan, dan kerelawanan, untuk mewujudkan filantropi transformatif yang berhasil mengubah kebajikan berorientasi amal menjadi program-program kreatif dan inovatif.]